2019
DOI: 10.1021/acs.energyfuels.9b00624
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Removal from Biogas Using Carbon Impregnated with Oxidants

Abstract: Hydrogen sulfide removal from small quantities of gas such as biogas or landfill gas is usually carried out via technologies based on its adsorption onto solid sorbents. Biogas or landfill gas has a high moisture content; thus, for H 2 S removal, nonpolar-activated carbon is the most suitable sorbent. However, the adsorption capacity of common activated carbon for H 2 S is small. Therefore, sorbents that have been properly impregnated are often used because they react with H 2 S to form various products. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The gas blending apparatus is made up of N 2 and H 2 S highpurity gases (1 and 2), two glass flowmeters (3 and 4), a blending chamber (5), and two switching valves (6 and 7). The photochemical bubbling scrubber is made up of a digital pH meter (8), a silicone plug (10), an ultraviolet light lamp (254 nm of wavelength, UVC; Shenzhen Sitong Technology Lighting Co., Ltd., China) with quartz protective tube (11), a glass bubbling column scrubber (inside diameter of 8.5 cm and height of 30 cm) (12), a porous bubbler (13) (the average aperture is 20−40 μm), a peristaltic pump (15), and a solution tank (16). The temperature regulating apparatus has a thermocouple (9), and a temperature control water tank (14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas blending apparatus is made up of N 2 and H 2 S highpurity gases (1 and 2), two glass flowmeters (3 and 4), a blending chamber (5), and two switching valves (6 and 7). The photochemical bubbling scrubber is made up of a digital pH meter (8), a silicone plug (10), an ultraviolet light lamp (254 nm of wavelength, UVC; Shenzhen Sitong Technology Lighting Co., Ltd., China) with quartz protective tube (11), a glass bubbling column scrubber (inside diameter of 8.5 cm and height of 30 cm) (12), a porous bubbler (13) (the average aperture is 20−40 μm), a peristaltic pump (15), and a solution tank (16). The temperature regulating apparatus has a thermocouple (9), and a temperature control water tank (14).…”
Section: Methodsmentioning
confidence: 99%
“…Hydrogen sulfide (H 2 S) can not only corrode equipment and deactivate catalysts but also endanger human health and pollute the environment. To reduce H 2 S emission, a large number of H 2 S purification technologies have been developed. Traditional H 2 S separation processes mainly include adsorption/catalytic desulfurization, biological desulfurization, , membrane separation, , and chemical scrubbing desulfurization. The adsorption desulfurization technology is a simple process and has a low investment, but its regeneration energy consumption is high, and the adsorbent is easily inactivated. , The biological desulfurization technology can be operated under normal temperature and pressure with low operating cost and does not easily cause secondary pollution but is time-consuming and inefficient with high H 2 S concentration. , The membrane separation method has the advantages of simple operation, high separation efficiency, and no pollution but has the disadvantages of poor corrosion resistance, short life, and high cost. , Wet scrubbing desulfurization technology has many advantages, such as simple operation, strong adaptability, and high removal efficiency, and is the most widely used and most mature technology at present. , However, the most commonly used traditional absorbers, such as alkanolamine, carbonate, etc., have high regeneration energy consumption and quite strong corrosiveness. Some relatively new reagents, such as ionic liquids and complexing agents, have quite high cost and regeneration loss and still find difficulty in large-scale applications. , …”
Section: Introductionmentioning
confidence: 99%
“…4,5 Biogas containing high concentrations of H 2 S could corrode gas pipes, mechanical devices, and engines, and thus, it must be purified before its further utilization. 6 A wide range of desulfurization techniques have been applied, but the significant drawbacks with maintenance complexity, high cost, and the secondary pollution have restricted their application. 7 So far, a cost-effective approach for removing H 2 S from the AD of chicken manure has remained a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…In China, around 155 million tons of chicken manure are produced annually, and regarding its higher potential biogas production (794 mL/gVS), chicken manure is deemed to be a suitable substrate for AD treatment. In addition, recent studies indicated that the AD of chicken manure was successful even under stressed conditions such as high ammonia level. , However, AD of chicken manure generates biogas with H 2 S as high as 5000–6000 ppm, which is much higher than that produced from the AD of diary manure (2000–4000 ppm) and sewage sludge (2500–4900 ppm). , Biogas containing high concentrations of H 2 S could corrode gas pipes, mechanical devices, and engines, and thus, it must be purified before its further utilization . A wide range of desulfurization techniques have been applied, but the significant drawbacks with maintenance complexity, high cost, and the secondary pollution have restricted their application .…”
Section: Introductionmentioning
confidence: 99%
“…Maize cob waste physically activated was found to have promising results in H 2 S removal from biogas [16]. Also, H 2 S adsorption by carbon impregnated with oxidants was performed in [17] whereby the reaction conditions are very important for better sorption capacity. Biochar derived from leaf waste was tested for adsorption of hydrogen sulphide [18] whereby 84.2% H 2 S was effectively removed from biogas at a carbonization temperature of 400°C.…”
Section: Introductionmentioning
confidence: 99%